Doppler ultrasound in pregnancy – quality requirements of DEGUM and clinical application (part 2) - Faber, Renaldo; Heling, Kai-Sven; Steiner, Horst; Gembruch, Ulrich (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
This second part on Doppler sonography in prenatal medicine and obstetrics reviews its clinical applications. While this has not become the initially anticipated screening tool, it is used for the diagnosis and surveillance of a variety of fetal pathologies. For example, the sonography-based determination of uterine artery blood flow indices is an important parameter for the first trimester multimodal preeclampsia risk assessment, increasing accuracy and providing indication for the prophylactic treatment with aspirin. It also has significant implications for the diagnosis and surveillance of growth-restricted fetuses in the second and third trimesters through Doppler-sonographic analysis of umbilical artery, middle cerebral artery and ductus venosus. Here, especially the hemodynamics of the ductus venosus provides a critical criterium for birth management of severe, early-onset FGR before 34 + 0 weeks of gestation. Further, determination of maximum blood flow velocity of the middle cerebral artery is a central parameter in fetal diagnosis of anemia which has been significantly improved by this analysis. However, it is important to note that the mentioned improvements can only be achieved through highest methodological quality. Importantly, all these analyses are also applied to twins and higher order multiples. Here, for the differential diagnosis of specific complications such as TTTS, TAPS and TRAP, the application of Doppler sonography has become indispensable. To conclude, the successful application of Doppler sonography requires both exact methodology and precise pathophysiological interpretation of the data.Im 2. Teil zum Einsatz der Methode der Dopplersonografie in der Pränatal- und Geburtsmedizin geht es um den klinischen Einsatz. Die Erwartungen einer breiten Anwendung der Methode als Screeningverfahren haben sich nicht bestätigt. Allerdings spielen die Widerstandsindizes der Aa. uterinae im Rahmen eines multimodalen Ansatzes für die Vorhersage der Präeklampsie im 1. Trimester eine wichtige Rolle, verbessern die Genauigkeit und schaffen die Grundlage für eine effektive Prophylaxe mit Aspirin. Für die Zustandsdiagnostik und Überwachung wachstumsretardierter Föten im 2. und 3. Trimester hat die Dopplersonografie der A. umbilicalis, A. cerebri media und des Ductus venosus eine herausragende Bedeutung. Insbesondere die Hämodynamik des Ductus venosus ist ein entscheidendes Kriterium für das Geburtsmanagement der frühen, schweren IUGR vor 34 SSW. Die maximale Geschwindigkeit in der A. cerebri media ist der zentrale Parameter in der fetalen Anämiediagnostik und hat deren Qualität grundlegend verändert und verbessert. Allerdings sind diese Verbesserungen an eine hohe methodische Qualität der Messung gekoppelt. Dies alles trifft natürlich auch für Zwillinge und höhergradige Mehrlinge zu. Die differenzierte Diagnostik spezifischer Komplikationen von monochorialen Mehrlingen wie FFTS, TAPS und TRAP ist ohne den Einsatz der Dopplersonografie nicht mehr zu denken. Der Erfolg des vielfältigen Einsatzes der Dopplersonografie ist verknüpft mit exakter methodischer Anwendung und präziser pathophysiologischer Interpretation.
Keywords: dopplersonography; fetal surveillance; guideline; clinical application